Solve for z -1z+1=11

Math
-1z+1=11
Rewrite -1z as -z.
-z+1=11
Move all terms not containing z to the right side of the equation.
Tap for more steps…
Subtract 1 from both sides of the equation.
-z=11-1
Subtract 1 from 11.
-z=10
-z=10
Multiply each term in -z=10 by -1
Tap for more steps…
Multiply each term in -z=10 by -1.
(-z)⋅-1=10⋅-1
Multiply (-z)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1z=10⋅-1
Multiply z by 1.
z=10⋅-1
z=10⋅-1
Multiply 10 by -1.
z=-10
z=-10
Solve for z -1z+1=11

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top